Molecular data from the holotype of the enigmatic Bornean Black Shrew, Suncus ater Medway, 1965 (Soricidae, Crocidurinae), place it in the genus Palawanosorex - Jonathan A, Nations; Thomas C., Giarla; Muhd Amsyari, Morni; Julius, William-Dee; Mark T., Swanson; Anna E., Hiller; Faisal Ali, Anwarali Khan; Jacob A., Esselstyn (Pensoft Publishers, 2022)
Although Borneo has received more attention from biologists than most other islands in the Malay Archipelago, many questions regarding the systematic relationships of Bornean mammals remain. Using next-generation sequencing technology, we obtained mitochondrial DNA sequences from the holotype of Suncus ater, the only known specimen of this shrew. Several shrews collected recently in Sarawak are closely aligned, both morphologically and mitochondrially, with the holotype of S. ater. Phylogenetic analyses of mitochondrial sequences indicate that the S. ater holotype and new Sarawak specimens do not belong to the genus Suncus, but instead are most closely related to Palawanosorex muscorum. Until now Palawanosorex has been known only from the neighboring Philippine island of Palawan. Additional sequences from nuclear ultra-conserved elements from the new Sarawak specimens strongly support a sister relationship to P. muscorum. We therefore transfer ater to Palawanosorex. The new specimens demonstrate that P. ater is more widespread in northern Borneo than previously recorded. Continued sampling of Bornean mammal diversity and reexamination of type material are critical in understanding the evolutionary history of the biologically rich Malay Archipelago.